Convergence in Motion: A Review of Fair Value Levels' Relevance. (2nd September 2021) - Filip, Andrei; Hammami, Ahmad; Huang, Zhongwei; Jeny, Anne; Magnan, Michel; Moldovan, Rucsandra
ABSTRACT: The IFRS 13 post-implementation review by the IASB motivates our investigation on the value relevance of fair value (FV) measurement hierarchy (i.e. level 1, level 2, and level 3). First, using a meta-analysis, which allows us to summarize inconsistent empirical findings, we synthesize studies on the value relevance of the FV hierarchy. Overall, value relevance is lower for level 3 than for levels 1 and 2, but it increases over time. In non-U.S. studies, we note lower value relevance across all levels of FV assets. Underlying asset fundamentals, model risk, and measurement process complexity may contribute to this value relevance gap. Second, from interviews with professionals from financial institutions, we note that, in practice, there has been extensive learning about FV accounting since the 2007–9 Financial Crisis and a formalization of the valuation process that the academic literature has yet to fully recognize. We thus highlight conceptual and methodological issues and areas for research with practical implications.